KONSEP KOMPETENSI KEPRIBADIAN GURU DALAM KITAB ADABUL ’ALIM WAL MUTA’ALLIM KARYA K.H. M. HASYIM ASY’ARI - Chanan, Abdul; Hifza, Hifza; Irawan, Deni (ILJ: Islamic Learning Journal, 2024)
One of the four teachers' competences mandated by the laws and regulations of the government is the competence of the teacher's personality. The human tendency is to imitate someone's behavior. This is the crucial role of a teacher. The Book of Adabul Alim Wal Muta’allim is the work of Indonesian great scholar K.H.M. Hasyim Asy’ari who discusses the Akhlak of teachers and pupils. The focus of this research is to know the competence of teachers in the book Adabul 'Alim Wal Muta'allim and the relevance with Permendiknas No. 16 Year 2007 This research uses a qualitative approach and the type of research is research library (library research). Data collection techniques use document analysis techniques and data analysis using content analysis. The results of this study found, that the competence of the personality of the teacher, can be seen through the 20 points mentioned in the book Adabul 'Alim Wal Muta'allim by K.H. M. Hasyim Asy'ari. These points include spiritual aspects (muqarabah, khauf, sakinah, wa’, tawadhu’, khusuk, tawakkal), not greed, not humiliation, zuhud, away from lowly and humble work, preserving reputation, conducting Islamic scholarship, pursuing religious teachings consistently, treating others well, cleansing yourself from corrupt morals, enthusiasm in learning, not hesitating to ask questions, and contributing to the writing of scientific works. While its relevance to government regulations especially Permendiknas No. 16 of 2007, there is a relevance between these regulations and the competence of the personality of teachers found in the book of Adabul ‘Alim Wal Muta’allim